Industrial talk: Aerospace and composite industry / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2022)
The objectives of the webinar were to give exposure to the students about the application of science and technolo-gy skills in industrial sector and a culture of knowledge and experience sharing between the industry practitioners and academicians as well as the students. This promotes and establishes a good relationship between industries or external agencies and Faculty of Applied Sciences, UiTM Perak Branch Tapah Campus. Dr Mohammad Ham-dan bin Sanusi, Deputy General Manager/Head of Program Management of CTRM Aero-composites, Melaka, began the webinar by giving his speech about his portfo-lio, introduction to aerospace, aircraft industry and such.